Pre-procedural ATI score (age-thrombus burden-index of microcirculatory resistance) predicts long-term clinical outcomes in patients with ST elevation myocardial infarction treated with primary percutaneous coronary intervention. (15th September 2021) - Montalto, Claudio; Kotronias, Rafail A.; Marin, Federico; Terentes-Printzios, Dimitrios; Shanmuganathan, Mayooran; Emfietzoglou, Maria; Scalamera, Riccardo; Porto, Italo; Langrish, Jeremy; Lucking, Andrew; Choudhury, Robin; Kharbanda, Rajesh; et al.
Abstract: Background: The ATI (Age-Thrombus burden-Index of Microvascular Resistance [IMR]) score was developed to predict suboptimal myocardial reperfusion in patients with ST-Elevation Myocardial Infarction (STEMI). When applied in the early phases of revascularization (e.g. before stent insertion), it predicts which patients are most likely to have a larger infarct size. In this study, we assessed the score's utility in determining which STEMI patients are at highest risk of clinical events during follow-up. Methods: The ATI-score was calculated prospectively in 254 STEMI patients using age (>50 years = 1 point), pre-stenting IMR (>40 U and < 100 U = 1 point; ≥100 U = 2 points) and angiographic thrombus score (4 = 1 point, 5 = 3 points); the cohort was stratified in high vs. low-intermediate ATI-score strata (≥4 vs. < 4, respectively). Results: After 3 years of follow-up, patients with high ATI-score presented a higher rate of Major Adverse Cardiac Events (MACE) defined as the composite of all-cause mortality, resuscitated cardiac arrest and new heart failure diagnosis (Hazard Ratio [HR]: 3.07; 95% Confidence Interval [CI]: 1.19–7.93; p = 0.02). The ATI-score showed a moderate discriminative power (c-stat: 0.69), not significantly different from that of other risk scores used in the STEMI setting. A high ATI-score was an independent predictor of MACE (HR: 3.24; 95% CI: 1.22–8.58; p = 0.018). Conclusions: The ATI-score can discriminate patients at higher risk of long-term adverse events. The score allows predication of subsequent events even before coronary stenting, and consequently it may allow the option of individualized therapy in the early stages of the clinical care-pathway. Highlights: The ATI-score (ATIs) is calculated using pre-stenting IMR, age and thrombus burden score The ATIs can be used in STEMI patients to predict microvascular dysfunction and infarct size A high ATIs was independently associated with increased MACE at long term follow-up The ATIs had a moderate discriminative power, not significantly different from other risk scores Our results allow to individualize therapy in the early stages of the clinical care-pathway.